Hepatoprotective Effect of Kaempferol: A Review of the Dietary Sources, Bioavailability, Mechanisms of Action, and Safety - Maulana Yusuf Alkandahri; Barolym Tri Pamungkas; Zulpakor Oktoba; Mareetha Zahra Shafirany; Lela Sulastri; Maya Arfania; Ebta Narasukma Anggraeny; Ade Pratiwi; Fitri Dwi Astuti; null Indriyani; Siti Yuliani Dewi; Salsa Zulfa Hamidah (Advances in Pharmacological and Pharmaceutical Sciences)
The liver is the body’s most critical organ that performs vital functions. Hepatic disorders can affect the physiological and biochemical functions of the body. Hepatic disorder is a condition that describes the damage to cells, tissues, structures, and functions of the liver, which can cause fibrosis and ultimately result in cirrhosis. These diseases include hepatitis, ALD, NAFLD, liver fibrosis, liver cirrhosis, hepatic failure, and HCC. Hepatic diseases are caused by cell membrane rupture, immune response, altered drug metabolism, accumulation of reactive oxygen species, lipid peroxidation, and cell death. Despite the breakthrough in modern medicine, there is no drug that is effective in stimulating the liver function, offering complete protection, and aiding liver cell regeneration. Furthermore, some drugs can create adverse side effects, and natural medicines are carefully selected as new therapeutic strategies for managing liver disease. Kaempferol is a polyphenol contained in many vegetables, fruits, and herbal remedies. We use it to manage various diseases such as diabetes, cardiovascular disorders, and cancers. Kaempferol is a potent antioxidant and has anti-inflammatory effects, which therefore possesses hepatoprotective properties. The previous research has studied the hepatoprotective effect of kaempferol in various hepatotoxicity protocols, including acetaminophen (APAP)-induced hepatotoxicity, ALD, NAFLD, CCl4, HCC, and lipopolysaccharide (LPS)-induced acute liver injury. Therefore, this report aims to provide a recent brief overview of the literature concerning the hepatoprotective effect of kaempferol and its possible molecular mechanism of action. It also provides the most recent literature on kaempferol’s chemical structure, natural source, bioavailability, and safety.